Strategies of Nirma to Become Goliath - Kaura, Vinita (Prabandhan: Indian Journal of Management, 2009)
The paper aims at developing insight about whether local brands can survive in presence of global brands or not. Indian market is flooded with a variety of foreign goods, and in this scenario, Indian brands are fighting for survival. But it is possible for local brands to survive if they can study the business environment thoroughly and accordingly decide their strategies with innovation. This paper deals with strategies of Nirma that has helped it in surviving in spite of presence of HLL (now HUL).